2011
DOI: 10.1093/cid/ciq027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of 2009 Pandemic Influenza A (pH1N1) and Seasonal Influenza Using Rapid Influenza Antigen Tests, San Antonio, Texas, April–June 2009

Abstract: Clinicians frequently use influenza rapid antigen tests for diagnostic testing. We tested nasal wash samples from 1 April to 7 June 2009 from 1538 patients using the QuickVue Influenza A+B (Quidel) rapid influenza antigen test and compared the results with real-time reverse transcription polymerase chain reaction (rRT-PCR) assay (gold standard). The prevalence of 2009 pandemic influenza A (pH1N1) was 1.98%, seasonal influenza type A .87%, and seasonal influenza type B 2.07%. The sensitivity and specificity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Lucas et al reported that the sensitivity and specificity for the detection of H1N1 was 20.0% and 99.0%, respectively, using the QuickVue Influenza A+B Test (Quidel), while other investigators have found its sensitivity to be higher than this value. (7)(8)(9) In one study, the Actim Influenza A&B kit (Medix Biochemica, Joensuu, Finland) has been shown to be 90.0% sensitive for the detection of influenza A virus. (10) Some small studies have shown that a positive RAT spurs changes in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Lucas et al reported that the sensitivity and specificity for the detection of H1N1 was 20.0% and 99.0%, respectively, using the QuickVue Influenza A+B Test (Quidel), while other investigators have found its sensitivity to be higher than this value. (7)(8)(9) In one study, the Actim Influenza A&B kit (Medix Biochemica, Joensuu, Finland) has been shown to be 90.0% sensitive for the detection of influenza A virus. (10) Some small studies have shown that a positive RAT spurs changes in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…During the 2009 pandemic, attack rates among military personnel measured during clusters of infection among specific military units ranged from as low as 3% [7] and as high as 70% [8]. In confined settings, such as aboard navy ships, serologic attack rates of influenza among US and foreign military crew have been estimated to be between 30–50% [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…l Comparison of estimates of sensitivity of POCTs for the detection of influenza A and B suggested that kits may detect influenza A more readily than influenza B -Influenza A: 81% (95% CI 64% to 91%); Influenza B: 59% (95% CI 47% to 70%). l Analyses of five studies 152,182,198 that included both adults and children and compared the Quidel POCT with PCR produced an overall pooled sensitivity of 34% (95% CI 14% to 62%) and specificity of 99% (95% CI 97% to 100%), which are much more similar to those obtained in 3WS.…”
mentioning
confidence: 75%